Creating a toolkit with stakeholders for leveraging tablet computers to support person-centred dementia care in hospitals. (October 2020) - Shadarevian, John; Chan, Cheryl; Berndt, Annette; Son, Cathy; Gregorio, Mario; Horne, Neil; Mann, Jim; Wallsworth, Christine; Chow, Bryan; O'Neill, Ryan; Hung, Lillian
Introduction: People with dementia may refuse care because they feel overwhelmed by an unfamiliar environment. Everyday technology such as tablets have the potential to support person-centred dementia care in hospitals. Aims: We aimed to identify barriers and enabling factors in order to develop a toolkit to support the use of tablets in engaging individual and group activities, especially to play family videos, for hospitalized older people with dementia. Methods: A participatory action research approach was employed. We facilitated staff focus groups and conducted interviews with stakeholders. A toolkit was developed based on participants' perspectives on how to support successful adoption. Results: Our analysis identified two enabling factors: users' engagement in developing a toolkit for support and adapting implementation to meet local needs. Barriers included staff and family inexperience, mechanical instability of hardware, issues around privacy and data access, technology use and personalization of messages. The toolkit includes short videos, a brochure for family caregivers, and a pocket card for staff. Discussion and implications: Staff, family and patients start with varying levels of experience with the use of tablets, making education and support vitally important to implementation. Health organizations should involve staff, patients, and families to find practical solutions.